2013
DOI: 10.1080/03601234.2013.761877
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous detection and degradation patterns of kresoxim-methyl and trifloxystrobin residues in citrus fruits by HPLC combined with QuEChERS

Abstract: This study aimed to investigate the residues, kinetics and dissipation patterns of kresoxim-methyl, (E)-methoxyimino[α-(o-tolyloxy)-o-tolyl]acetate, and trifloxystrobin, methyl(E)-methoxyimino-{(E)-α[1-(α,α,α-trifluoro-m-tolyl)ethylideneaminooxy]-o-tolyl}acetate". A simple and sensitive liquid chromatography-ultraviolet detection (LC-UV) method combined with the 'Quick Easy Cheap Effective Rugged and Safe' (QuEChERS) protocol was developed to quantify the levels of kresoxim-methyl and trifloxystrobin residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…The present results are anticipated since QuEChERS is selective towards carbendazim and chlorpyrifos [33,34,35], and showed that the level of carbendazim and chlorpyrifos residues in all selected samples are below than the EU legal limit. There was a permissible occurrence of carbendazim and chlorpyrifos residues in parsley which grown without application of any pesticide.…”
Section: Sample Analysismentioning
confidence: 55%
“…The present results are anticipated since QuEChERS is selective towards carbendazim and chlorpyrifos [33,34,35], and showed that the level of carbendazim and chlorpyrifos residues in all selected samples are below than the EU legal limit. There was a permissible occurrence of carbendazim and chlorpyrifos residues in parsley which grown without application of any pesticide.…”
Section: Sample Analysismentioning
confidence: 55%
“…For fruits with peels, for instance citrus, the previous works demonstrated that the pesticide residues were mainly in the peels, and only little in the pulps. Zhu and others () found more than 97% of the kresoxim‐methyl and trifloxystrobin deposits gradually dissipated from the citrus peels within 15 d. The half‐lives of kresoxim‐methyl and trifloxystrobin in the peels were in the ranges of 2.63 to 2.66 d and 3.12 to 3.15 d, respectively. The kresoxim‐methyl and trifloxystrobin residues in the pulp dissipated to a level below 0.01 mg/kg after 9 d. However, there are few information about the pesticide behaviors in oil plants.…”
Section: Introductionmentioning
confidence: 96%
“…Information on dissipation kinetics of pesticides in food crops and other plants is a key aspect in current risk assessment. There were many reports on pesticide degradation (Munitz and others ; Zhu and others ), metabolism (Liu and others ), adsorption (Uchimiya and others ; Marin‐Benito and others ) in different agricultural plants and soils. Most of pesticides degraded fast in plants and soils.…”
Section: Introductionmentioning
confidence: 99%
“…Annual production of fresh citrus fruit in China is more than 26.5 million tons [1]. Citrus fruits in China are frequently encroached by mites, such as Panonychus citri (McGregor) (Acari: Eriophyidae), Phyllocoptruta oleivora Ashmead (Acari: Eryiophyidae) and Polyphagotarsonemus latus (Banks) (Acari: Tarsonemidae) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%